The Electrical And Structural Properties Of Aluminium And Nitrogen Doped Zinc Oxide Thin Film Prepared By Radio Frequency Sputtering - Low, Lynn Yien (2013)
Zinc Oxide (ZnO) is an attractive semiconductor for various applications due to its direct wide band gap (3.37 eV) and high exciton binding energy (60 meV). Thus, realization of reproducible and good p-type ZnO is important for the formation of homo p-n junction in electronic and opto-electronic devices. However, ZnO exhibits intrinsic n-type conductivity, low acceptors solubility and compensation effect that have hindered research on the materials and device development. The main objective of this research work is to fabricate high quality p-type ZnO using a new approach in an oxygen (O) rich growth environment by RF magnetron sputtering. The structural, electrical and optical properties of the fabricated ZnO film were characterized. The acceptor doped ZnO thin films on glass substrate were fabricated by the RF sputtering of ZnO target in N2O/Ar gas environment. The variation of substrate temperature (room temperature to 400 ºC) and gas ratio of N2O (0 - 70%) were applied in order to determine the optimum process variables for the deposition of p-type nitrogen doped ZnO (NZO). Aluminium (Al) metal target with different RF power (0 – 110 W) was used for the deposition of aluminium and nitrogen doped ZnO (ANZO) thin films at different Al concentration in order to compare with single doped ZnO